An investigation of the attenuation characteristics of distant ground motions in Peninsular Malaysia by comparing Values of recorded with estimated PGA and PGV - Zaini Sooria, Shaerliza (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2010)
The development of a design motion requires some input on ground motion characteristics. For a country such as Malaysia, where historical data is lacking and seismic activities are low, the information on characteristics of ground motion may be obtained by utilizing established attenuation relationships. This study aims to investigate the characteristics of distant ground motions in Peninsular Malaysia, which originated from the active tectonic plate of Sumatra, by comparing recorded peak ground acceleration (PGA) and peak ground velocity (PGV) values with those estimated using four attenuation models. Selected attenuation models are the Atkinson and Boore (1995), the Taro et al. (1997), the Dahle et al. (1990), and the Si and Midorikawa (1999) models. The analysis for comparison was made by employing a maximum of 46 horizontal component accelerograms, recorded at 14 seismic stations. These are data derived from 15 interplate earthquakes between May 2004 and July 2007. Recorded PGA and PGV values were plotted on respective attenuation curves to examine ground motion attenuation characteristics. Results indicated that attenuation models, established for stable tectonic regions, provide good estimation of PGA and PGV for Sumatran earthquakes for magnitude range of 5.9 to 9.0. The study shows that the Dahle et al. (1990) model best represents the characteristics of ground motions in terms of PGA, while the Atkinson and Boore (1995) model gives appropriately estimate ground motions in tenus ofPGY.